Screening of Ionic Liquids for Acid Gas Removal - Giuseppe Andriani; Gianmaria Pio; Chiara Vianello; Ernesto Salzano; Paolo Mocellin (Chemical Engineering Transactions, 2025)
To mitigate the environmental impacts of human activities, it is essential to carefully treat vented gaseous streams to prevent the release of undesired or toxic compounds into the atmosphere. These harmful chemicals can react with atmospheric elements such as oxygen or moisture, forming acids that pose significant environmental risks. Such acids can cause degradation of soils, contamination of surface and groundwater bodies, and damage to human-made structures and facilities. Therefore, developing and deploying technologies designed to remove the precursors of these polluting substances is paramount. Although several alternatives currently exist for this purpose, they often suffer from limitations such as low reusability, limited affinity for specific molecules, and inadequate absorbent capacity for effectively capturing the full range of pollutants in gaseous streams. In light of these challenges, ionic liquids (ILs) have emerged as promising candidates for the selective and quantitative capture of pollutants. ILs offer distinct advantages, including their ability to be tailored for specific applications through chemical structure modifications, enhancing their selectivity and absorption capacity. However, to advance the development of sustainable capture technologies, it is crucial to thoroughly evaluate the absorption performance and physicochemical properties of ILs. This evaluation is necessary to identify the most effective ILs for pollutant capture and ensure that the selected materials can be used sustainably over the long term. In addition to their absorption efficiency, the thermal stability of ILs must be rigorously assessed to guarantee their durability and reliability in industrial applications. Given these considerations, the present study undertakes a critical screening of various ILs for acid gas capture to identify the most suitable candidates for further research and potential industrial implementation, with a specific focus on SO2 capture. This screening process involves a comprehensive analysis of ILs based on key parameters, including their acid gas absorption capacity, the experimental conditions under which they operate (such as temperature and partial pressure of the treated gases), and their viscosity and density. By categorizing ILs according to these criteria, the study aims to pinpoint the ideal candidates for subsequent, more detailed thermal stability assessments, having the goal of advancing the field of acid gas capture by identifying ILs that demonstrate superior absorption performance and exhibit the necessary thermal stability for sustainable and long-term use in industrial processes.